Perfectly matched inhomogeneous receiving metasurface for line source incidence - Shiwei Dong (Wiley, 2021)
Abstract This paper presents a perfectly matched inhomogeneous receiving metasurface for line source incidence, based on the effective medium equivalency. Each building block of the inhomogeneous metasurface has effective constitutive parameters that satisfy a specific relationship dependent on the location of the line source. By doing so, the reflection from the receiving metasurface for the cylindrical wave incidence can be significantly suppressed, improving the total reception efficiency greatly. Theoretical analysis, numerical calculation, full‐wave simulations and experimental results are consistent with each other, showing promising applications in some short‐range wireless power transmission systems, where the incident wave is non‐planar.